Leptin receptor polymorphism increases the risk of painful symptoms in Brazilian women with endometriosis - Jéssica Vilarinho Cardoso; Daniel Escorsim Machado; Fernanda Nunes de Almeida; Plínio Tostes Berardo; Rui Medeiros; Jamila Alessandra Perini (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: Endometriosis pain is associated with inflammatory cytokines, such as leptin (LEP), through activation with its receptor (LEPR), and its expression can be influenced by the presence of genetic polymorphisms. Therefore, this study aims to evaluate the role of the LEP rs7799039 and LEPR rs1137100 polymorphisms in the painful symptoms of endometriosis in Brazilian women. Methods: A retrospective study was carried out in two Brazilian public hospitals with 237 cases of endometriosis, divided into two comparison groups according to the painful symptoms associated with the disease (absence or presence of severe and disabling symptoms). Genetic analysis was performed by real-time PCR technique, and association analyses were estimated using odds ratio (OR) and 95% confidence interval (CI), using a non-conditional logistic regression model. Results: Endometriosis cases showed a high prevalence of painful symptoms: 82% dysmenorrhea, 67% dyspareunia, 53% chronic pelvic pain, and 52% cyclical intestinal and 25% urinary complaints. Regarding genetic analyses, cases had 32.7% of the A allele and 11.4% of the AA genotype for the LEP rs7799039 G>A SNP, and 17.5% of the G allele and 2.5% for of GG genotype for the LEPR rs1137100 A>G SNP. There is a significant association of the LEPR rs1137100 polymorphism with chronic pelvic pain (OR=1.75; CI 95%=1.05-2.89) and dyspareunia (OR=1.78; CI 95%=1.01-3.12) in women with endometriosis. Conclusion: Our findings suggest that the LEPR rs1137100 polymorphism is associated with increased endometriosis-related gynecological pain and may be a potential target for molecular diagnosis of the disease and development of individualized treatment strategies.